Proper Choice of Vessels for Supermicrosurgery Training: An Experimental Animal study - Ha, Yooseok; Song, Seung Han; Kang, Nak Heon; Oh, Sang-Ha (Journal of Reconstructive Microsurgery, 2018)
Background Reconstruction using supermicrosurgery, a technique of microneurovascular anastomosis for smaller vessels (< 0.8 mm), has become popular. Experimental animal studies for supermicrosurgery training have been reported; however, there have been few studies performed according to vessel diameter and pedicle length. In this study, the external diameters of four vessels (femoral, superficial epigastric, axillary, and common thoracic) and pedicle length of two flaps (superficial epigastric and common thoracic–long thoracic) were measured.Methods The inguinal and pectoral regions of Sprague-Dawley rats (n = 19) were dissected anatomically, and the external diameters of the four vessels were measured (right and left, artery and vein measured separately). After elevating the superficial epigastric and common thoracic–long thoracic flaps, the pedicle length of the flaps was also measured.Results Among the 16 vessels examined, the external diameters of 11 and 5 vessels were above and below 0.8 mm, respectively. The external diameters of the superficial epigastric vessel and common thoracic vessel (both arteries and veins) were below 0.8 mm. The external diameters of the femoral and axillary vessels (veins) were above 0.8 mm. The length of the common thoracic–long thoracic pedicle was approximately10 mm longer than that of the superficial epigastric pedicle.Conclusions The external diameters of the superficial epigastric vessel and common thoracic vessel are small enough for supermicrosurgery training. The pedicle lengths of both the superficial epigastric and common thoracic–long thoracic flaps are sufficient to perform free flap experiments. Supermicrosurgical free flaps using these two vessels and a study of the physiology and pharmacology of the flaps will likely be possible in the future.
Keywords: microsurgery; training; laboratory rats